THE IMPACT OF INTELLECTUAL CAPITAL PERFORMANCE ON INTELLECTUAL CAPITAL DISCLOSURE IN FINANCIAL REPORT (CASE STUDY ON BANKING SECTOR COMPANIES REGISTERED ON THE INDONESIA STOCK EXCHANGE) - Gorethai, Jasslynia (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2019)
This research aims to know the potential effect of Intellectual Capital Performance (ICP) to the intensity of Intellectual Capital Disclosure (ICD). The independent variables used in this research are the components of ICP that consists of Value Added Human Capital (VAHU), Value Added Capital Employed (VACA), and Structural Capital Value Added (SCVA) that is measured by using the Value Added Intellectual Coefficient (VAIC?). While, the dependent variable used in this research is ICD that measured by a disclosure index and relevant scoring system. Company size and leverage are also used in the regression model as moderating variables. One year annual reports (2017) of banking sector companies registered on the Indonesia Stock Exchange (IDX) are analyzed in quantitative research type. The samples that listed on the IDX in 2017 are selected by using purposive sampling method with certain criteria and 33 banking sector companies are obtained. The analysis is made by multiple regression analysis and the data testing is conducted by using SPSS 22 and Eviews 9 which previously has been carried out the classic assumption test first. Results of this study indicate that: (1) Simultaneously, ICP component significantly affect ICD. However, each component of VAHU and SCVA does not significantly affect the ICD, only VACA significantly affects the ICD; (2) Simultaneously, with the moderation of company size, ICP does not significantly affect the ICD. Similarly, each component of VAHU, VACA and SCVA does not significantly affect ICD; and (3) Simultaneously, with the moderation of company leverage, ICP significantly affects ICD. However, each component of VAHU and SCVA does not significantly affect the ICD, only VACA significantly affects the ICD.Keywords: Intellectual Capital Performance (ICP), Intellectual Capital Disclosure (ICD), Value Added Human Capital (VAHU), Value Added Capital Employed (VACA), Structural Capital Value Added (SCVA).Abeysekera, I. (2010). The Influence of Board Size on Intellectual Capital Disclosure by Kenyan Listed Firms. Journal of Intellectual Capital, 11 (4), pp. 504-518.Abeysekera, I., & Guthrie, J. (2004). Human Capital Reporting in a Developing Nation. British Accounting Review, 36 (3), pp. 251-268.Aditya Reza, R. (2010). Pengaruh Gaya Kepemimpinan, Motivasi, dan Disiplin Kerja terhadap Kinerja Karyawan PT. Sinar Santosa Perkasa Banjarnegara. Semarang: Universitas Diponegoro.Agnes, U. (2008). Sebuah Tinjauan Akuntansi Atas Pengukuran dan Pelaporan Knowledge. The 2nd National Conference UKWMS. Surabaya.Al-Ali, N. (2003). Comprehensive Intellectual Capital Management. New Jersey, Hoboken: Wiley.Alfaih, M. (2016). The Effectiveness of Board of Directors? Characteristics in Mandatory Disclosure Compliance. Journal of Financial Regulation and Compliance, 24 (2), pp. 154-176.Alfraih, M. (2018). Intellectual Capital Reporting and Its Relation to Market and Financial Performance. International Journal of Ethics and Systems, 34 (3), pp. 266-281.Alwert, K., Bornemann, M., & Kivikas, M. (2004). Intellectual Capital Statement - Made in Germany. Berlin: Federal Ministry for Economics and Technology.Andriessen, D. (2004). Making Sense of Intellectual Capital: Designing a Method for the Valuation of Intangibles. Oxford: Elsevier Butterworth.Andriyanto, R., & Metalia, M. (2011). Perbandingan Tingkat Kelengkapan Mandatory Disclosure dan Voluntary Disclosure Informasi Akuntansi. Jurnal Akuntansi dan Investasi, 12 (1), pp. 15-35.Arjuwati, B. (2016). Pengaruh Kinerja Intellectual Capital Terhadap Intellectual Capital Disclosure pada Perusahaan yang Listing di Bursa Efek Indonesia. Padang: Kementerian Riset, Teknologi dan Pendidikan Tinggi Politeknik Negeri Padang.Ballow, J., Burgman, R., & Molnar, M. (2004). Managing for Shareholder Value: Intangibles, Future Value and Investment Decisions. Journal of Business Strategy, 25 (3), pp. 26-34.Barney, J. (1991). Firm Resources and Sustained Competitive Advantage. Journal of Management, 17 , pp. 99-120.Barney, J., & Arikan. (2001). The Resource-based View: Origins and Implications. Strategic Management Journal, 7 (16), pp. 124-188.Barney, J., & Clark, D. (2007). Resource-based Theory: Creating and Sustaining Competitive Advantage. New York: Oxford University Press, Inc.Bestivano, W. (2013). Pengaruh Ukuran Perusahaan, Umur Perusahaan, Profitabilitas, dan Leverage Terhadap Perataan Laba pada Perusahaan yang Terdaftar di BEI (Studi Empiris pada Perusahaan Perbankan di BEI). Padang: Universitas Negeri Padang.Boedi, S. (2008). Pengungkapan Intellectual Capital dan Kapitalisasi Pasar. Semarang: Universitas Diponegoro.Bontis, N., Keow, W., & Richardson, S. (2000). Intellectual Capital and Business Performance in Malaysian Industries. Journal of Intellectual Capital, 1 (1), pp. 85-100.Brigham, E., & Houston, F. (2001). Manajemen Keuangan. Jakarta: Erlangga.Brooking, A. (1996). Intellectual Capital: Core Assets for the Third Millennium Enterprise. London: Thomson Business Press.Bruggen, A., Vergauwen, P., & Dao, M. (2009). Determinants of Intellectual Capital Disclosure: Evidence from Australia. Management Decision, 47 (2), pp. 233-245.Cahyati, A. (2012). Intellectual Capital: Pengukuran, Pengelolaan dan Pelaporan. Jurnal Riset Akuntansi & Komputerisasi Akuntansi, 3 (1).Carlucci, D., Marr, B., & Schiuma, G. (2004). The Knowledge Value Chain: How Intellectual Capital Impacts on Business Performance. International Journal of Technology Management, 27 (6/7), pp. 575.Chen, M., Cheng, S., & Hwang, Y. (2005). An Empirical Investigation of the Relationship Between Intellectual Capital and Firm?s Market Value and Financial Performance. Journal of Intellectual Capital, 6 (2), 159-176.Chu, S. K., Chan, K. H., & Wu, W. W. (2011). Charting Intellectual Capital Performance of the Gateway to China. Journal of Intellectual Capital, 12 (2), pp. 249-276.Connelly, C., Zweig, D., Webster, J., & Trougakos, J. (2012). Knowledge Hiding in Organizations. Journal of Organizational Behavior, 33, pp. 64-88.Cresswell, J. (2009). Research Design Qualitative, Quantitative, and Mixed Methods Approaches (Third ed.). United States: SAGE Publications, Inc.Crilly, D., & Sloan, P. (2013). Autonomy or Control? Organizational Architecture and Corporate Attention to Stakeholders. Organization Science, 25, pp. 339-355.Deegan, C. (2004). Financial Accounting Theory. Sydney: McGraw-Hill Book Company.Denziana, A., & Yunggo, E. (2017). Pengaruh Profitabilitas, Struktur Aktiva, dan Ukuran Perusahaan Terhadap Struktur Modal Perusahaan pada Perusahaan Real Estate and Property yang Terdaftar di Bursa Efek Indonesia Tahun 2015. Jurnal Akuntansi & Keuangan, 8 (1), pp. 51-67.Dewi, D. (2010). Pengaruh Jenis Usaha, Ukuran Perusahaan dan Financial Leverage Terhadap Tindakan Perataan Laba Pada Perusahaan Yang Terdaftar di Bursa Efek Indonesia (Studi Empiris di Bursa Efek Indonesia). Semarang: Universitas Diponegoro.Donaldson, T., & Preston, L. (1995). The Stakeholder Theory of the Corporation: Concepts, Evidence, and Implications. Academy of Management Review, 20, pp. 65?91.Edvinson, L. (1997). Developing Intellectual Capital at Skandia. Long Range Planning, 30 (3), pp. 366-373.Edvinsson, L., & Malone, M. (1997). Intellectual Capital: Realizing your Company?s True Value by Finding Its Hidden Brainpower. New York: Harper Business.Evans, T. G. (2003). Accounting Theory: Contemporary Accounting Issues . South-Western, Thomson, Australia.Fama, E., & Jensen, M. (1983). Separation of Ownership and Control. Journal of Law and Economics, 26 (2), pp. 301-325.Ferdinand, A. (2006). Metode Penelitian Manajemen. Semarang: Badan Penerbit Universitas Diponegoro.Freedman, M., & Jaggi, B. (2005). Global Warming, Commitment to The Kyoto Protocol, and Accounting Disclosures by The Largest Global Public Firms from Polluting Industries. The International Journal of Accounting, 40 , pp. 215-232.Freeman, R. (1984). Strategic Management: A Stakeholder Approach. Boston: Pitman.Freeman, R., & Reed. (1983). Stockholders and Stakeholders: A New Perspective on Corporate Governance. Californian Management Review, 25 (2), pp. 88-106.Freeman, R., Harrison, J., & Wicks, A. (2007). Managing for Stakeholders: Survival, Reputation, and Success. London and New Haven: Yale University Press.Garcia-Ayuso, M. (2002). Factor explaining the in ethical valuation of intangibles. Sevilla: Department of Accounting and Financial Economics, Universidad De Sevilla.Gates, S., & Langevin, P. (2010). Human Capital Measures, Strategy and Performance: HR Managers' Perceptions. Accounting, Auditing & Accountability Journal, 23 (1), pp. 111-132.Ghozali, I. (2013). Aplikasi Analisis Multivariate dengan Program SPSS Cetakan VII. Semarang: Badan Penerbit Universitas Diponegoro.Ghuthrie, J., & Petty, R. (2001). Intellectual Capital: An Australian Annual Reporting. Journal of Inttelectual Capital, 8 (2), pp.272-87.Goh, P., & Lim, K. (2004). Diclosing Intellectual Capital in Company Annual Reports: Evidence from Malaysia. Journal of Intellectual Capital, 5 (3), pp. 500-510.Guthrie, J., & Petty, R. (2000). Intellectual Capital: Australian Annual Reporting Practices. Journal of Intellectual Capital, 1 (3), pp. 241-251.Guthrie, J., Cuganesan, S., & Ward, L. (2006). Legitimacy Theory: A Story of Reporting Social and Environmental Matters Within the Australian Food and Beverage Industry. Sydney: The University of Sydney.Guthrie, J., Petty, R., Yongvanich, K., & Ricceri, F. (2004). Using Content Analysis as a Research Method to Inquire to Intellectual Capital Reporting. Journal of Intellectual Capital, 5 (2), pp. 282-293.Hafni, A. (2018). Pengaruh Pengungkapan Sustainability Reporting dan Intellectual Capital Terhadap Nilai Perusahaan (Studi Empiris Perusahaan Sektor Pertambangan yang Terdaftar di BEI Tahun 2011-2015). Yogyakarta: Universitas Negeri Yogyakarta.Haji, A. A., & Mubaraq, S. (2012). The Trends of Intellectual Capital Disclosures: Evidence from the Nigerian Banking Sector. Journal of Human Resource Costing & Accounting, 16(3), pp. 184-209.Hall, M., Millo, Y., & Barman, E. (2015). Who and What Really Counts? Stakeholder Prioritization and Accounting for Social Value. Journal of Management Studies, 52 (7), pp. 907-934.Haniffa, R., & Cooke, T. E. (2005). The Impact of Culture and Governance on Corporate Social Reporting. Journal of Accounting and Public Policy, 24 , pp. 391-430.Harisnawati, R., Ulum, I., & Syam, D. (2017). Pengaruh Intellectual Capital Performance Terhadap Intensitas Pelaporan Modal Intelektual. Jurnal Reviu Akuntansi, 7 (1), pp. 941-950.Hariyanto, W., & Hermawan, S. (2012). Pengaruh Intellectual Capital Terhadap Business Performance Dan Competitive Advantage Pada Perusahaan Farmasi Di Jawa Timur. Sidoarjo: Universitas Muhammadiyah Sidoarjo.Healy, P., & Palepu, K. (2001). Information Asymmetry, Corporate Disclosure, and the Capital Markets. Journal of Accounting & Economics, 31 (1/3), pp. 405-440.Henri, J. (2006). Management Control Systems and Strategy: A Resource-based Perspective. Accounting, Organizations, and Society, 31, pp. 529-558.Husin, N., Ahmad, N., & Sapingi, R. (2011). Intellectual Capital: A Focus on Human Capital Reporting Practices of Top Malaysian Listed Companies. The South East Asian Journal of Management, 5 (1), pp. 51-71.Ikatan Akuntan Indonesia. (2017). Standar Akuntansi Keuangan. Jakarta: Ikatan Akuntan Indonesia.Indonesian Institute of Accountants. (2009). PSAK. Jakarta: IAI.Jawahar, I., & McLaughlin, G. (2001). Toward a Descriptive Stakeholder Theory: An Organizational Life Cycle Approach. The Academy of Management Review, 26, pp. 397?414.Jensen, M., & Meckling, W. (1976). Theory of the Firm: Managerial Behavior, agency Costs and Ownership. Journal of Financial Economics, 3 (4), pp. 305-360.Jiao, Y. (2011). Corporate Disclosure, Market Valuation, and Firm Performance. Financial Management, 40 (3), pp. 647-676.Jihene, F., & Robert, P. (2013). The Effect of Intellectual Capital Disclosure on the Value Creation: An Empirical Study Using Tunisian Annual Reports. International Journal of Accounting and Financial Reporting, 3 (1), pp. 81-107.Kaufmann, L., & Schneider, Y. (2004). Intangibles: A Synthesis of Current Research. Journal of Intellectual Capital, 5 (3), pp. 366-388.Kementerian Keuangan Republik Indonesia Badan Pengawas Pasar Modal dan Lembaga Keuangan. (2012). Keputusan Ketua Badan Pengawas Pasar Modal dan Lembaga Keuangan Nomor: KEP-347/BL/2012.Khan, H. U., & Ali, M. M. (2010). An Empirical Investigation and Users' Perceptions on Intellectual Capital Reporting in Banks. Journal of Human Resource Costing & Accounting, 14 (1), pp. 48-69.Lev, B. (1999). The Inadequate Public Information on Intellectual Capital and Its Consequence. Conference Proceeding: Measuring and Reporting Intellectual Capital, Experience, Issues and Prospects, An International Symposium. Amsterdam: Organisation for Economic Cooperation and Development.Li, Z., Chen, Z., Lui, T., & Chu, S. (2016). The Impact of Intellectual Capital on Company?s Performances: A Study Based on MAKE Award Winners and non-MAKE Award Winner Companies. Procedia Computer Science 99, pp. 181 ? 194.Lin, C. Y., & Edvinsson, L. (2011). National Intellectual Capital: a Comparison of 40 Countries. Berlin, Germany: Springer.Muttakin, M., Khan, A., & Belal, R. (2015). Intellectual Capital Disclosure and Corporate Governance: An Empirical Examination. Victoria: Deakin University.Nurcholisah, K., & Yadiati, H. W. (2017). Intellectual Capital Disclosure and Information Asymmetry in General Banking Listed in Indonesia Stock Exchange. International Business Management, 11 (4), pp. 972-983.Oktavia, M., & Daljono. (2014). Pengaruh Intellectual Capital Terhadap Kinerja Keuangan, Pertumbuhan Dan Nilai Pasar Perusahaan (Studi Empiris pada Perusahaann Konstruksi, Property & Real Estate yang Terdaftar di Bursa Efek Indonesia Tahun 2009-2012). Diponegoro Journal of Accounting, 3 (3), pp. 1-15.Oktavianti, H., & Wahidahwati. (2014). Faktor-faktor yang Mempengaruhi Pengungkapan Intellectual Capital. Jurnal Ilmu & Riset Akuntansi, 3 (5), pp. 1-18.Otoritas Jasa Keuangan. (2017). Undang-Undang Nomor 20 Tahun 2008 Tentang Usaha Mikro, Kecil, dan Menengah. Otoritas Jasa Keuangan.Petty, R., & Guthrie, J. (2000). Intellectual Capital Literature Review: Measurement, Reporting, and Management. Journal of Intellectual Capital, 1 (1), pp. 155-176.Prabowo, D. (2014). Analisis Faktor-Faktor yang Mempengaruhi Intellectual Capital Disclosure dan Pengaruh Intellectual Capital Disclosure terhadap Market Capitalization (Studi Empiris pada Perusahaan Real Estate dan Properti di BEI Periode 2010-2012). Semarang: Universitas Diponegoro.Priyanti, S. (2015). Determinan Pengungkapan Modal Intelektual Berdasarkan Variabel Keuangan dan Non Keuangan (Studi Empiris pada Perusahaan Perbankan yang Listing di BEI Tahun 2011-2013). Semarang: Universitas Negeri Semarang.PT Bursa Efek Indonesia. (2018). Laporan Keuangan dan Tahunan. Retrieved from Bursa Efek Indonesia: http://www.idx.co.id/.Pulic, A. (2000). VAIC ? An Accounting Tool for IC Management. International Journal of Technology Management, 20 (5-8), pp. 702-714.Purnamawati, F. (2013). Analisis Intellectual Capital PT Wahyu Kreasi Utama, Jakarta. Jakarta: Universitas Indonesia.Purnomosidhi, B. (2006). Praktik Pengungkapan Modal Intelektual pada Perusahaan Publik di Bursa Efek Jakarta (BEJ). Jurnal Riset Akuntansi Indonesia, 9 (1), pp. 1-20.Puspitasari, A. (2018). The Practice of Disclosing Human Capital in Bank Jawa Barat and Banten: From the Perspective of Political Economy of Accounting. Pontianak: University of Tanjungpura.Ray, G., Barney, J., & Muhana, W. (2004). Capabilities, Business Process, and Competi-tive Advantage: Choosing The Dependent Variable in Empirical Test of The Resource-based View. Strategic Management Journal, 25, pp. 23-37.Razak, R. A., Mohammad, J., & Tobiagi, S. M. (2016). Intellectual Capital Dislosures Practices and Intellectual Capital Performance in Saudi Arabia Financial Institution. Journal of Business Studies Quarterly, 7(4), pp. 1-14.Sawarjuwono, T., & Kadir, A. (2003). Intellectual Capital: Perlakuan, Pengukuran dan Pelaporan (Sebuah Library Research). Jurnal Akuntansi dan Keuangan, 3 (1).Sawarjuwono, T., & Kadir, A. (2003). Intellectual Capital: Perlakuan, Pengukuran dan Pelaporan (Sebuah Library Research). Jurnal Akuntansi dan Keuangan, 5 (1), pp. 35?57.Schroeder, R., Bates, K., & Junttila, M. (2002). A Resource-based View of Manufacturing Strategy and the Relationship to Manufacturing Performance. Strategic Mana-gement Journal, 23, pp. 101-117.Setianto, A. (2014). Analisis Faktor-faktor yang Mempengaruhi Pengungkapan Modal Intelektual (Studi Empiris pada Perusahaan yang Terdaftar di